The use of a y chromosome specific DNA library in the study of sex abnormalities in particular the xx males - Vermaak, L. K (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. in Med. Sc.) -- University of Stellenbosch, 1987.